Alternative splicing: transcriptional regulatory network in agroforestry - Hussain, Syed Sarfaraz; Abbas, Manzar; Abbas, Sammar; Wei, Mingke; El-Sappah, Ahmed H.; Sun, Yuhan; Li, Yun; Ragauskas, Arthur J.; Li, Quanzi (Frontiers in Plant Science, 2023)
Alternative splicing (AS) in plants plays key role in regulating the expression of numerous transcripts from single gene in a regulatory pathway. Variable concentrations of growth regulatory hormones and external stimuli trigger alternative splicing to switch among different growth stages and adapt to environmental stresses. In AS phenomenon, spliceosome causes differential transcriptional modifications in messenger RNA (mRNAs), resulted in partial or complete retention of one or more introns as compared to fully spliced mRNA. Differentially expressed proteins translated from intron retaining messenger RNA (mRNAir) perform vital functions in feedback mechanism. At post-transcriptional level, AS causes remodeling of transcription factors (TFs) by addition or deletion of binding domains to activate and/or respress transcription. In this study, we have summarized the specific role of AS in regulation of gene expression through repression and activation of transcriptional regulatory network under external stimuli and switch among developmental stages.